CGE Assessment of Tourism Policies in Turkey - K.Ali Akkemik; Erisa Dautaj Şenerdem (European Regional Science Association (ERSA), 2014)
Turkey is among top ten countries in the world tourism market in terms of international tourist arrivals and international tourism revenues. Tourism sector has grown rapidly over the last three decades and emerged as an important foreign exchange earner. It is argued that tourism creates opportunities for employment and contributes to economic growth and international tourism revenues compensate part of the current account deficit, which has traditionally been a major source of structural problems in Turkey. Tourism policies, therefore, may have important implications at the macro level. Recently the government published a strategy paper for tourism titled "Tourism Strategy of Turkey - 2023". In this study, we critically analyze the tourism strategy of Turkey using a dynamic applied computable general equilibrium (CGE) model. The model is a multi-sector, multi-country CGE model based on the GTAP model. The model includes 14 sectors and 12 regions. The sectoral disaggregation of the model emphasizes tourism-related activities. We use the GTAP database and run policy simulations to assess alternative tourism strategies as well as the potential impacts of exogenous shocks. The results bear important policy implications for the economy. .
Keywords: C68; L83; 330